Cardiovascular risk factors in adolescents born preterm - Sipola-Leppänen, Marika; Vääräsmäki, Marja; Tikanmäki, Marjaana; Hovi, Petteri; Miettola, Satu; Ruokonen, Aimo; Pouta, Anneli; Järvelin, Marjo-Riitta; Kajantie, Eero (Pediatrics (Evanston), 2014)
Adolescents and adults born as small preterm infants show more pronounced risk factors of cardiovascular disease. Whether similar risks apply across all degrees of preterm birth is poorly known. We studied the association between preterm birth and cardiovascular risk factors in 6642 16-year-old adolescents of the population-based Northern Finland Birth Cohort 1986. Of these, 79 (1.2%) were born at <34 gestational weeks (early preterm), 238 (3.6%) at 34 to 36 weeks (late preterm), and 6325 at term (controls). Girls born early preterm had 6.7 mm Hg (95% confidence interval: 3.1-10.2) higher systolic blood pressure (BP) and 3.5 mm Hg (1.1-5.8) higher diastolic BP, but no difference in serum lipid levels compared with control girls. Boys showed no differences in BP, but boys born early preterm had 6.7% (0.2%-13.7%) higher total cholesterol, 11.7% (2.1%-22.3%) higher low-density lipoprotein cholesterol, and 12.3% (3.1%-22.4%) higher apolipoprotein B concentrations. The differences were similar (BP) or stronger (lipids) when adjusted for maternal smoking, birth weight SD score, parental education, pubertal stage, BMI, and lifestyle. There were similar associations with length of gestation as a continuous variable. Accordingly, mean differences between late preterm and controls were in the same direction but weaker, although most were not statistically significant. Preterm birth was associated with elevated BP in adolescent girls and an atherogenic lipid profile in boys. Because these associations were strongest among those born early preterm, our findings are consistent with a dose-response relationship between shorter length of gestation and cardiovascular risk factors.